Case report: Fetoscopic Laparoschisis (FETO-LAP): a new therapeutic route to explore for fetuses with severe diaphragmatic hernias - Kohl, Thomas; Riehle, Nadja; Messroghli, Leila; Maus, Sibylle; Otto, Christiane; Klinke Petrowsky, Michaela; Martel, Richard; Beck, Grietje; Boettcher, Michael; Schaible, Thomas (Children, 2023)
Background: The purpose of this report is to describe the seminal case of a near-term human fetus with a life-threatening left diaphragmatic hernia that underwent fetoscopic tracheal occlusion (FETO) combined with fetoscopic partial removal of herniated bowel from the fetal chest by fetoscopic laparoschisis (FETO-LAP). Case summary: A life-threatening left diaphragmatic hernia (liver-up; o/e LHR of ≤25%; MRI lung volume ≤ 20%) was observed in a human fetus at 34 weeks of gestation. After counselling the mother about the high risks of postnatal demise if left untreated, the expected limitations of fetoscopic tracheal occlusion (FETO), and the previously untested option of combining FETO with fetoscopic laparoschisis, i.e., partial removal of the herniated bowel from the fetal chest (FETO-LAP), she consented to the latter novel treatment approach. FETO-LAP was performed at 36 + 5 weeks of gestation under general maternofetal anesthesia. Mother and fetus tolerated the procedure well. The neonate was delivered and the balloon removed on placental support at 37 + 2 weeks of gestation. On ECMO, a rapid increase in tidal volume was seen over the next eight days. Unfortunately, after this period, blood clots obstructed the ECMO circuit and the neonate passed away. Discussion: This seminal case shows that in a fetus with severe left diaphragmatic hernia, partial removal of the herniated organs from the fetal chest is not only possible by minimally invasive fetoscopic techniques but also well tolerated. As the effect of FETO alone is limited in saving severely affected fetuses, combining FETO with fetoscopic laparoschisis (FETO-LAP) offers a new therapeutic route with multiple, potentially life-saving implications.